Introduction To The Science of Sufism (Tasavvuf İlmine Giriş), Dawūd Al-Qayṣarī, Trans. by Muhammed Bedirhan (Nefes Publications, Istanbul, 2013). - Chowdury, Saeyd Rashed Hasan (CenRaPS Journal of Social Sciences, 2024)
This paper analyses “Introduction to the Science of Sufism (Tasavvuf İlmine Giriş),” which comprises translations of two treatises by the renowned Sufi scholar Dawūd Al-Qayṣarī. A prominent follower of Ibn Arabi, Al-Qayṣarī was the chief instructor of the first madrasa in Iznik, established during the Ottoman Empire. His mystical interpretation of existence, deeply rooted in the concept of Wahdat al-Wujud (the Unity of Being), has significantly influenced Iranian, Arab, Turkish, and Indian cultures. The first treatise delves into topics such as the definition of Sufi science, the names and attributes of God, the degrees of existence, prophethood, sainthood, union, unity, and the role of the perfect human in the world. The second treatise offers a commentary on the initial sentence of a Quranic exegesis by Abdurrazzaq Kashani, Al-Qayṣarī’s sheikh, also framed within the Wahdat al-Wujud understanding. This analysis aims to provide a comprehensive overview of Al-Qayṣarī’s contributions to Sufi metaphysics and his profound influence on Islamic mysticism.